1987
DOI: 10.1192/bjp.150.6.824
|View full text |Cite
|
Sign up to set email alerts
|

Detention in Broadmoor

Abstract: When the length of stay of restricted patients admitted to Broadmoor under the legal category of psychopathic disorder was examined, the factor found to be of primary importance was the gravity of the admission offence. If the men's offences did not cause personal injury, they had a good chance of early release. Patients convicted of violent or sexual offences, and particularly those who attacked strangers, made up the great majority of the long-term group. For the mentally ill there was no relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 1 publication
0
15
1
Order By: Relevance
“…However, a number of studies have demonstrated that this LoS is far exceeded in a large proportion of cases (see literature review in Chapter 4). For high secure care, earlier studies have identified an average LoS of about 8 years 33 but, again, no shared standard exists as to from what LoS onwards individuals should be considered 'long-stay patients'.…”
Section: Long Stay In Forensic Settingsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a number of studies have demonstrated that this LoS is far exceeded in a large proportion of cases (see literature review in Chapter 4). For high secure care, earlier studies have identified an average LoS of about 8 years 33 but, again, no shared standard exists as to from what LoS onwards individuals should be considered 'long-stay patients'.…”
Section: Long Stay In Forensic Settingsmentioning
confidence: 99%
“…37,84,88,97 Two UK studies had samples drawn from a women's medium secure unit. 40,87 An earlier UK study of Broadmoor high secure patients by Dell et al 33 used an 8-year threshold, the authors observing that 53% of those with a 'psychopathic disorder' and 42% of those with a 'mental illness' classification of the (then) MHA were 'long-termers' who were detained for > 8 years. A threshold of 10 years was used in Germany by Ross et al, 93 who found that 15% of their sample had a LoS that exceeded 120 months.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations